Cloning and sequencing of a gene encoding a 21-kilodalton outer membrane protein from Bordetella avium and expression of the gene in Salmonella typhimurium. - Gentry-Weeks, C R (1992)
Three gene libraries of Bordetella avium 197 DNA were prepared in Escherichia coli LE392 by using the cosmid vectors pCP13 and pYA2329, a derivative of pCP13 specifying spectinomycin resistance. The cosmid libraries were screened with convalescent-phase anti-B. avium turkey sera and polyclonal rabbit antisera against B. avium 197 outer membrane proteins. One E. coli recombinant clone produced a 56-kDa protein which reacted with convalescent-phase serum from a turkey infected with B. avium 197. In addition, five E. coli recombinant clones were identified which produced B. avium outer membrane proteins with molecular masses of 21, 38, 40, 43, and 48 kDa. At least one of these E. coli clones, which encoded the 21-kDa protein, reacted with both convalescent-phase turkey sera and antibody against B. avium 197 outer membrane proteins. The gene for the 21-kDa outer membrane protein was localized by Tn5seq1 mutagenesis, and the nucleotide sequence was determined by dideoxy sequencing. DNA sequence analysis of the 21-kDa protein revealed an open reading frame of 582 bases that resulted in a predicted protein of 194 amino acids. Comparison of the predicted amino acid sequence of the gene encoding the 21-kDa outer membrane protein with protein sequences in the National Biomedical Research Foundation protein sequence data base indicated significant homology to the OmpA proteins of Shigella dysenteriae, Enterobacter aerogenes, E. coli, and Salmonella typhimurium and to Neisseria gonorrhoeae outer membrane protein III, Haemophilus influenzae protein P6, and Pseudomonas aeruginosa porin protein F. The gene (ompA) encoding the B. avium 21-kDa protein hybridized with 4.1-kb DNA fragments from EcoRI-digested, chromosomal DNA of Bordetella pertussis and Bordetella bronchiseptica and with 6.0- and 3.2-kb DNA fragments from EcoRI-digested, chromosomal DNA of B. avium and B. avium-like DNA, respectively. A 6.75-kb DNA fragment encoding the B. avium 21-kDa protein was subcloned into the Asd+ vector pYA292, and the construct was introduced into the avirulent delta cya delta crp delta asd S. typhimurium chi 3987 for oral immunization of birds. The gene encoding the 21-kDa protein was expressed equivalently in B. avium 197, delta asd E. coli chi 6097, and S. typhimurium chi 3987 and was localized primarily in the cytoplasmic membrane and outer membrane. In preliminary studies on oral inoculation of turkey poults with S. typhimurium chi 3987 expressing the gene encoding the B. avium 21-kDa protein, it was determined that a single dose of the recombinant Salmonella vaccine failed to elicit serum antibodies against the 21-kDa protein and challenge with wild-type B. avium 197 resulted in colonization of the trachea and thymus with B. avium 197.